COMMUNITY EMPOWERMENT COUNSELING MODEL IN BENEFICIARY GRADUATION AS A SUSTAINABLE POVERTY ALLEVIATION STRATEGY IN BANYUMAS REGENCY - Faishol, Lutfi; Alfi, Imam (Jurnal Al-Ijtimaiyyah, 2025)
This research is motivated by the high dependence of beneficiaries on social assistance. Beneficiary Families (KPM) face mental, psychological, and social obstacles in achieving economic independence after graduation, so that financial-based empowerment programs are considered ineffective. This study aims to describe the community empowerment counseling model in the social assistance process for beneficiary graduates to transition to sustainable independence. The research uses a descriptive qualitative method with data collection techniques through active observation, in-depth interviews, and documentation. The research subjects consisted of five sub-district level social companions and fifty families of graduates from ten communities in southern Banyumas. Data were analyzed by reducing, classifying, and mapping findings by linking field results with empowerment theory and community counseling practices. The study results show that empowerment counseling plays an important role in increasing participants' confidence, self-efficacy, and motivation to be economically independent through community-based productive activities. However, challenges in the form of social stigma, lack of family support, and limited market access still hinder the empowerment process. In conclusion, empowerment counseling has been carried out using a psychosocial approach that strengthens the beneficiaries' mental readiness and socioeconomic capacity. Scientifically, this research contributes to developing an integrative model between social empowerment theory and community counseling practices in supporting the sustainability of social welfare postgraduate programs at the local level.